The Effect of Steiner, Montessori, and National Curriculum Education Upon Children's Pretence and Creativity. (15th March 2015) - Kirkham, Julie Ann; Kidd, Evan
Abstract: Pretence and creativity are often regarded as ubiquitous characteristics of childhood, yet not all education systems value or promote these attributes to the same extent. Different pedagogies and practices are evident within the UK National Curriculum, Steiner and Montessori schools. In this study, 20 children participated from each of these school systems ( N  = 60, aged 6;10–8;11) completing the test of creative thinking—drawing production (TCT‐DP; K. K. Urban, & H. G. Jellen, 1996) and a pretend actions task (W. F. Overton & J. P. Jackson, 1973). Overall, Steiner pupils performed significantly higher on the TCT‐DP than both the Montessori and National Curriculum pupils who performed similarly. Steiner pupils also performed significantly better on the pretend actions task than the Montessori pupils, but no other significant differences were found. Overall, there was also a significant positive correlation between pretence and creativity in the current sample, supporting previous research suggesting that these skills are related (e.g., A.S. Kaugars & S. W. Russ, 2009; P. Y. Mullineaux & L. F. Dilalla, 2009).